Yeast flotation viewed as the result of the interplay of supernatant composition and cell-wall hydrophobicity - deSousa, SR; Oliveira, K. F.; Souza, C. S.; Kilikian, B. V.; Laluce, Cecília [UNESP] (Elsevier B.V., 2003)
Flotation is a process of cell separation based on the affinity of cells to air bubbles. In the present work, flotability and hydrophobicity were determined using cells from different yeasts (Hansenulla polymorpha, Saccharomyces cerevisiae, Candida albicans), which were propagated in different media and at different temperatures. Alterations to the supernatant of the cells were also carried out before the flotation assays. The results described here indicate that supernatants of the yeast cells can play a more important role on flotation than cell-wall hydrophobicity. For example, wall-hydrophobicity of strain FLT-01 of S. cerevisiae was high but flotation did not occur when their washed cells were resuspended in water. Additions of neopeptone to cultures of S. cerevisiae and H. polymorpha repressed flotation and increased the volume of foam. An additional task of the present work was to show that the relationship between cell-wall hydrophobicity and flotation performance was dependent on the method used for the measurement of hydrophobicity. Based on the assay procedure, two types of hydrophobicity were distinguished: (a) the apparent hydrophobicity for cells suspended in the medium and expressed by the degree of cell affinity to the organic solvent in the two-phase system supernatant/hexane; (b) the standard hydrophobicity, which was determined for cells suspended in a standard solution (acetate buffer, in the present work) within the acetate buffer/hexane system. Flotation of cells of S. cerevisiae and C albicans were best related to the degree of apparent hydrophobicity (varying with the supernatant composition at the cell/medium interface) rather than to the degree of standard hydrophobicity (varying with the alterations in the wall components, since the liquid phase was constant in the assay). However, depending on the yeast unpredictable results can be obtained. For example, cells of H. polymorpha exhibited good flotation associated to a high degree of standard hydrophobicity while having a lower degree of apparent hydrophobicity. Concerning growth temperature, flotation of cells of C albicans was strongly repressed when the temperature was raised from 30 to 38 degreesC while a similar effect was not observed in cultures of S. cerevisiae and H. polymorpha. It is difficult to understand and predict flotation of yeast cells but simple modifications made to the supernatant of cultures can activate or repress flotation. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: flotation; hydrophobicity; Saccharomyces cerevisiae; Hansenula polymorpha; Candida albicans